Evaluating air cleaner effectiveness in schools: a comprehensive review and protocol of a cluster-randomized controlled trial of physicochemical and microbial markers - Esmée Rianne Janssen; Kimberly J. Linde; Marcel G. L. C. Loomans; Wietske Dohmen; Lützen Portengen; Lili Xia; Jan F. L. Diepens; Dick J. J. Heederik; Twan van Hooff; Inge M. Wouters; Lidwien A. M. Smit (Frontiers in Public Health, 2026)
In school environments, characterized by high occupancy and prolonged exposure, airborne contaminants pose risks to respiratory health and learning outcomes. Portable air cleaners (PACs) are increasingly considered as a supplement to ventilation, yet field-based evidence remains heterogeneous, with few randomized trials and limited data on microbial agents. Here, we describe the design and methodology of a large-scale cluster-randomized controlled trial evaluating PAC effectiveness in Dutch primary school classrooms. The study included 180 classrooms across 29 primary schools, with classrooms clustered within schools and randomized to HEPA-filter PACs, ionization/plasma PACs, or no PACs. The design incorporated a three-week baseline or two-week post-intervention control period, and three repeated three-week intervention periods in the main phase, totaling up to 14 weeks per school. PACs were pre-tested under standardized laboratory conditions, screened for safety, and operated at comparable clean air delivery rates (CADR). Airborne dust was collected using electrostatic dust fall collectors (EDCs) and analyzed for bacterial markers representing common human microbiome constituents, a general bacterial indicator, and viral markers for seasonal infections. In 12 classrooms, active air sampling was conducted alongside EDCs to validate and quantify passive measurements. Continuous monitoring of particulate matter (PM₁₀, PM₄, PM₂.₅, PM₁), CO₂, air temperature, relative humidity, and volatile organic compounds (VOCs) was performed. Classroom-level absenteeism and parent-reported respiratory symptoms were collected retrospectively. Weekly national infectious-disease surveillance and outdoor PM and NO₂ data will contextualize indoor measurements and health outcomes. Hierarchical mixed-effects models accounting for school, cluster, and classroom structure will analyze microbial outcomes. Bayesian hierarchical models may be applied for values outside the quantifiable range. By integrating comprehensive indoor air quality assessment with a dual-control design distinguishing pre-existing classroom differences from temporal trends, this registered trial ( ClinicalTrials.gov , NCT07479420; 6 March 2026) provides a rigorous framework to evaluate PACs under real-world classroom conditions and support evidence-informed strategies to improve classroom indoor air quality. Clinical trial registration : https://clinicaltrials.gov/study/NCT07479420?term=air%20cleaner&viewType=Card&intr=air%20cleaner&rank=4 , ClinicalTrials.gov, NCT07479420.